Microfinance, sustainable development and poverty alleviation in Nigeria: proposal for a Maqasid ash-Shari’ah based (MSB) model - Adewale, Abideen Adeyemi; Daud, Mustafa (2010)
Nigeria is one of the countries having over 50 percent of her population suffering from poverty. Obviously, there have been serious efforts on the part of the government and other stakeholders in Nigeria at combating this socially menacing scourge of poverty. There is no doubt that by the overwhelming proportion and dimension, the trends in the incidence of poverty in Nigeria typify an intergenerational transmission given that there has arguably been more of poverty elevation than alleviation, especially when we critically examine the various policies and programs of Nigerian government in the last 25 years. These various policies and programs, however, appear to have discountenanced the relevance of sustainable livelihoods especially as per their financing from the Islamic perspective. This paper, therefore, evaluates both the impact of having access to, and the perception of some Muslim micro entrepreneurs in Ilorin metropolis on the pertinence of the Islamic micro financing alternative, which could serve as a viable economic mechanism and tool for the promotion of growth and Sustainable Development. Using Structural Equation Modeling (SEM), the study revealed that poverty; proxy by items related to the annual average household expenditure is statistically different among those who once had access to informal Islamic microfinance. Hence, micro credit access may be said to help alleviate poverty. This implies that Islamic micro finance albeit on a rather informal manner actually impacts positively on poverty alleviation. In view of this, the appositeness of an Islamic microfinance model based on the Maqasid ash-Shari’ah is advanced as a viable alternative to break away from the shackles of poverty. This study, therefore,without prejudice to the efficacy of conventional micro-financing concluded that Islamic microfinance alternative holds great prospects for poverty alleviation in Nigeria, particularly in the predominantly Muslim states like Kano, Katsina, Sokoto, Zamfara, Bauchi, Yobe, Borno etc. Some of the recommendations made include: the need to integrate Islamic microfinance scheme into the mainstream; enhancing the mass awareness through the print and electronic media on the need for Islamic MFIs; and sincerity on the part of the government to ensure that the criteria for the establishment of Islamic MFIs are not too stringent.